2D Germanane Derivative as a Vector for Overcoming Doxorubicin Resistance in Cancer Cells. (September 2020) - Fojtů, Michaela; Balvan, Jan; Raudenská, Martina; Vičar, Tomáš; Šturala, Jiří; Sofer, Zdeněk; Luxa, Jan; Plutnar, Jan; Masařík, Michal; Pumera, Martin
Highlights: Carboxtylic moiety modified 2D Germanene was prepared This 2D Germanene derivative was used to load doxorubicine This hybrid was used for cancer treatment Abstract: Cancer resistance to chemotherapeutics is a common problem often encountered in the clinical setting, hampering greatly the conventional therapy of malignant diseases for several decades. No generally efficient mechanism solving this phenomenon was found so far. Cancer cells can adapt to a stress applied in the form of chemotherapeutics and become insensitive to their effects. Under such a selection pressure, the cancer cells acquire features helping them not only to survive the changes in the environment but also to further divide and to form secondary lesions. Therefore, besides developing novel chemotherapeutics, refining the drug delivery mechanisms of the conventional ones is absolutely crucial to defeat the cancer, so we can fully benefit from the effects these therapeutics offer. Here, we demonstrated enhanced delivery of doxorubicin (DOX) to a DOX-resistant ovarian cancer cell line using completely novel 2D material 4-carboxybutylgermanane (Ge-Bu-COOH). In our study, we present Ge-Bu-COOH as a drug carrier evincing high drug-loading efficiency, low cytotoxicity up to the concentration of 2.5 μg/mL and no hemolysis. Simultaneously, binding DOX to Ge-Bu-COOH increases DOX accumulation in the DOX-resistant cell lines. It leads to a significant anticancer efficiency enhancement in A2780/ADR DOX-resistant cell line; with the maximal effect reaching up to 62.8% compared to free DOX. These findings have profound influence on understanding the behaviour of doxorubicin-resistant tumours and open new horizon to manage their treatment. Graphical abstract: Image, graphical abstract